More frequent moments in the climate change debate as emissions continue - Chris Huntingford; Pierre Friedlingstein (Environmental Research Letters, 2015)
Recent years have witnessed unprecedented interest in how the burning of fossil fuels may impact on the global climate system. Such visibility of this issue is in part due to the increasing frequency of key international summits to debate emissions levels, including the 2015 21st Conference of Parties meeting in Paris. In this perspective we plot a timeline of significant climate meetings and reports, and against metrics of atmospheric greenhouse gas changes and global temperature. One powerful metric is cumulative CO _2 emissions that can be related to past and future warming levels. That quantity is analysed in detail through a set of papers in this ERL focus issue. We suggest it is an open question as to whether our timeline implies a lack of progress in constraining climate change despite multiple recent keynote meetings—or alternatively—that the increasing level of debate is encouragement that solutions will be found to prevent any dangerous warming levels?